Book reviews - Lundgren, Svante; Martola, Nils (Nordisk judaistik/Scandinavian Jewish Studies, 1991)
The generation: the rise and fall of the generation of Jewish communists of Poland (Jaff Schatz, 1989) is reviewed by Svante Lundgren.Press mot friheten: opinionsbildning i de svenska tidningarna och åsiktsbrytningar om minoriteter 1772–1786 (Magnus Nyman, 1988) is reviewed by Nils Martola.Short notice by Nils Martola.